Pembuatan Direktori Batik di Museum Adityawarman - Muliawan, Budi; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about making of batik at Adityawarman museum directory, describe the process of making batik in Adityawarman museum directory with facilitate the retrieval of information contained in batik collection Adityawarman Museum. Methods of this paper is using descriptive method and get the data by observation, interview and collect data directly from the original source, which is a collection of batik contained in Adityawarman Museum. Based on analyzing the data, it can be concluded that in the process of making Directory Batik Adityawarman museum necessary steps as follows: 1) surveying batik collection through the inventory book etnografika collate and classify the data collection of batik collection names common in sequential order with the amount of the collection; 2) define the elements of what will be Â making the directory corresponding to the data already obtained the author uses elements such as the author listed as follows: the name of the general collection; registration number; inventory numbers; batik size; batik material; place of origin of batik is made; place of origin obtained batik and batik collection of photos.Keyword: directory; batik; Museum Adityawarman